Antibiotic screening of urine culture as a useful quality audit - Godwin Wilson; Shaherudeen Badarudeen; Angela Godwin (Journal of Infection in Developing Countries)
Introduction: The diagnosis of urinary tract infections includes microbiologic culture of urine to determine the etiology of the infection. However, interpretation of the results can be confounded by various factors including the accuracy of a patient's history of current antibiotic usage.